THE INFLUENCE OF THE GOVERNMENT'S INTERNAL CONTROL SYSTEM ON THE REALIZATION OF GOOD UNIVERSITY GOVERNANCE MODERATED BY DIGITAL TRANSFORMATION (SURVEY OF HIGHER EDUCATION UNITS IN CENTRAL SULAWESI) - Betty, Betty; Ridwan, Ridwan; M. Iqbal A; Femilia, Femilia; Fikry, Fikry (International Journal of Social Science, 2024)
This research aims to test and analyze "The Influence of the Government's Internal Control System on Good University Governance Moderated by Digital Transformation (Survey of Higher Education Units in Central Sulawesi)". This type of research is quantitative research. This research was carried out using survey and questionnaire methods as a tool to obtain data. The number of samples taken using census techniques was 59 higher education institutions in Central Sulawesi. The analytical tool used to process the data is WrapPLS software. The results of this research indicate that the Government's Internal Control System (control environment, control activities, risk assessment, information and communication, and monitoring) has a significant effect on good university governance. Digital transformation can moderate or strengthen the relationship between the Government's Internal Control System (control environment, control activities, risk assessment, information and communication, and monitoring) on ​​good university governance